An Integrated Study of the Eolian Dust in Pelagic Sediments From the North Pacific Ocean Based on Environmental Magnetism, Transmission Electron Microscopy, and Diffuse Reflectance Spectroscopy. Issue 5 (29th May 2018) - Zhang, Qiang; Liu, Qingsong; Li, Jinhua; Sun, Youbin
Abstract: Eolian dust is a major terrigenous component in North Pacific Ocean pelagic sediments and is an important recorder of Asian terrestrial environmental evolution and Northern Hemisphere atmospheric circulation. In order to extract and quantify wind‐borne mineral signals and develop a reliable eolian dust proxy for pelagic sediments, we investigated sediments from Ocean Drilling Program Hole 885A, North Pacific Ocean, by integrating results from environmental magnetism, transmission electron microscopy, and diffuse reflectance spectroscopy (DRS). Our results indicate that ferrimagnetic and antiferromagnetic minerals coexist in the sediments. The former includes biogenic magnetite, nano‐sized single domain (titano) magnetite inclusions embedded in silicate hosts, submicron vortex state magnetite, and ultrafine superparamagnetic maghemite. The latter includes hematite and goethite. Our results indicate that magnetic properties can be used to determine an overall trend of increased eolian dust inputs, with additional significant influence from biogenic and volcanogenic components. In contrast, a newly proposed parameter Rel Hm+Gt (combined hematite and goethite concentration) obtained from DRS measurements extracts precisely the eolian signal and precludes other components. Our DRS results indicate that hematite/goethite and siliceous fractions deposited at Hole 885A were jointly delivered to the North Pacific Ocean from Asian dust sources. Therefore, we suggest that Rel Hm+Gt is a reliable eolian dust proxy for pelagic sediments in this region. Key Points: Ferrimagnetic and antiferromagnetic minerals were identified systematically in North Pacific Ocean pelagic sediments Ferrimagnetic minerals record the overall trend of increased eolian dust inputs since the late Pliocene A parameter obtained from diffuse reflectance spectroscopy is proposed to trace eolian dust in pelagic sediments